Wear characteristics, reduction techniques and its application in automotive parts – A review - Luke O. Ajuka; Temitayo S. Ogedengbe; Timothy Adeyi; Omolayo M. Ikumapayi; Esther T. Akinlabi (Cogent Engineering, 2023)
AbstractWear phenomenon impact the operating efficiency and service life of engineering materials due to the influence of surface interaction at different working conditions. Successive tribological studies on wear-resistant materials in the last decade is estimated at approximately 40% of friction and wear, including laboratory tests. Most locally improvised wear testers in accordance with American Society for Testing and Materials (ASTM) and European (EN) standards, though, achieve 95–97% parametric accuracies with reduced cost, they hardly harmonize degradation and Archards coefficients for all possible wear factors, providing little data for simulation of mechanical and chemical wears which are responsible for non-uniform aggregation of wear patterns in practice. Complexities of intermeshing factors which combine to influence the effectiveness of developed test devices span over loads, speeds, temperatures, pressures, and ambience for various applications. This study highlights the techniques of wear characterization, test standards, and wear reduction with emphasis on surface texturing for improved eta/beta phase re-arrangements at low working temperatures in the enhancement of grain contraction during high bias-voltage cathodic substrate multi-phase coating, phosphating during pretreatments using peening techniques, residual stress reduction during cryogenic heat treatments as well as the impact of suitable architectural matrix composite strengthening, microstructures, and material reinforcements as suitable factors to influence improved tribological behaviors in materials. Optimal additive manufacturing (AM‐fabricating) techniques with pretreatments, thermal cycling, and tempering can engineer enhanced anti-tribocorrosion in automotive components.